The role of tacit knowledge in group innovation - Leonard, Dorothy
The complexity of skills and processes needed in the development of today's products and services requires that managers attend to the role of tacit knowledge during innovation. Knowledge held in people's bodies and heads, our unarticulated knowledge, is the very basis of creativity and is not easily captured nor codified. The process of innovation is both an exploration and synthesis. This article examines ways in which managers can begin to deal with tacit knowledge; how to create an environment for a divergent process that includes a wide and healthy proliferation of ideas and a successful convergent process in which options are narrowed and a solution is decided upon and implemented.